Pengembangan Modul Pengelolaan Praktek Kerja Lapangan Pada Sistem Informasi Akademik Perguruan Tinggi (Studi Kasus : STIKI) - Dedy Ari Purnomo; Nataniel David Tektanto; Koko Wahyu Prasetyo; Hilman Nuril Hadi (J-INTECH ( Journal of Information and Technology), 2023)
Professional internship is one of the compulsory courses that need to be taken by any student at STIKI as a requirement to graduate. STIKI offers two kind of program that can be taken to accomplish this course, namely PPK (Proyek PKL Kerjasama) and PPM (Proyek PKL Mandiri). Both submission and working processes of those programs are very different, as a result, the administration process of those two are resolved separately even when those programs are still called professional internship. There is another problem related to professional internship, mentoring for each program also cannot be done optimally due to many factors, as a result, lecturers can’t evaluate the result of each of their mentored teams optimally. To answer those problems, an information system can be used as one of the solutions. The system needs to be able to manage both submissions of those programs, manage the mentoring of each program, and also manage processes in final seminar submission and project completion for both programs. Since STIKI does not have this kind of system before, this system is expected to be able to fulfill the needs of field practice management at this college.